Efficacy of Dose-Titrated Glucagon Infusions in the Management of Congenital Hyperinsulinism: A Case Series - Salomon-Estebanez, Maria; Yau, Daphne; Dunne, Mark J.; Worth, Chris; Birch, Sune; Walewski, José L.; Banerjee, Indraneel (Frontiers in Endocrinology, 2020)
Background: Congenital hyperinsulinism (CHI), a rare disease of excessive and dysregulated insulin secretion, can lead to prolonged and severe hypoglycaemia. Dextrose infusions are a mainstay of therapy to restore normal glycaemia, but can be associated with volume overload, especially in infants. By releasing intrahepatic glucose stores, glucagon infusions can reduce dependency on dextrose infusions. Recent studies have reported positive outcomes with glucagon infusions in patients with CHI; however, to date, there are no reports describing the clinical utility of titrated doses of infused glucagon to achieve glycaemic stability. Objective: To assess the potential clinical utility of dose-titrated glucagon infusions in stabilising glycaemic status in paediatric patients with CHI, who were managed by medical and/or surgical approaches. Methods: Patients with CHI (N=33), with or without mutations in the ATP-sensitive K+ channel genes, ABCC8 and KCNJ11 requiring glucagon by dose titration in addition to intravenous dextrose and medical therapy with diazoxide/octreotide to achieve glycaemic stability were recruited. Following glucagon titration and a 24 hour glucose stable period, glucose infusion rate (GIR) was reduced over a 24 hour period. Achievement of glycaemic stability and decrease in GIR were considered end points of the study. Results: All patients achieved glycaemic stability with glucagon infusion, demonstrating clinical benefit. GIR reduced from 15.6 (4.5) to 13.4 (4.6) mg/kg/min mean (SD) (p=0.00019 for difference; n=32; paired t-test) over 24 hours. By univariate analysis, no individual baseline characteristic was associated with changes in the GIR. However, by baseline-adjusted modelling, mutational status of the patient (p=0.011) was inversely associated with a reduction in GIR. Adverse events were infrequent with diarrhoea possibly attributed to glucagon treatment in one patient. In long term treatment following GIR reduction, necrolytic migratory erythema was observed in another patient. Conclusion: These data suggest that dose-titrated glucagon infusion therapy aids hypoglycaemia prevention and reduction in GIR in the clinical management of patients with CHI.